Root and canal anatomy of mandibular first molars using micro-computed tomography: a systematic review - AL-Rammahi, Hasan M.; Chai, Wen Lin; Nabhan, Mohamed Shady; Ahmed, Hany M. A. (BMC oral health, 2023)
A thorough understanding of root and canal anatomy is crucial for successful root canal treatment outcomes. This systematic review aims to explore the published micro-CT studies investigated the anatomy of root and canal system in permanent mandibular first molars. An electronic search was performed on Web of science, PubMed, and Scopus. Micro-CT journal studies investigated the root and canal anatomy of permanent double-rooted mandibular first molars were included. Data on study characteristics, objectives of interest, specifications of the studies, and micro-CT specifications were extracted. Risk of bias assessment (ROB) of the included studies was performed using Anatomical Quality Assessment (AQUA) tool. The extracted data were presented in tables and figures to present and synthesise the results. A meta-analysis was performed for the studies related to the prevalence of Vertucci's canal configurations, middle mesial canal (MMC) configurations, and Fan's isthmus types. Amongst 1358 identified studies, thirty met the inclusion criteria. In terms of the objectives, the selected studies showed high anatomical variability in mandibular first molars. Twenty-two (73%), 25 (83%), and 12 (40%) of the studies reported the population/ethnicity, micro-CT specifications, and ethical approval, respectively. 28 (93%) studies did not disclose the method of sample size estimation. In only 6 (20%) of the studies, the authors had calibrated the assessment approaches. Mostly, a potential ROB was reported in domain 1 (objective(s) and subject characteristics) and domain 3 (methodology characterization). Whilst, low risk was reported in domains 2 (study design), 4 (descriptive anatomy), and 5 (reporting of results). The overall ROB was reported to be ''moderate'' in the vast majority of the studies (27/30). Meta-analysis results showed high levels of heterogeneity among the studies related to MMCs (I = 86%) and Fan's isthmus (I = 87%). As for the root canal configuration, pooled prevalence showed that Vertucci type IV and type I were the most prevalent in mesial and distal root canals, respectively. Based on moderate risk of bias level of evidence, micro-CT studies have shown wide range of qualitative and quantitative data presentations of the roots and canals in mandibular first molars. Protocol and registration. The protocol of this systematic review was prospectively registered in the Open Science Framework database ( https://osf.io ) on 2022-06-20 with the registration number 10.17605/OSF.IO/EZP7K.